Evaluating the relevance of species sorting and physiological plasticity of phytoplankton communities grown in a multifactor environment. (10th August 2021) - Marzetz, Vanessa; Wacker, Alexander
Abstract: The two important mechanisms influencing the response of phytoplankton communities to alterations of abiotic factors in their environment are difficult to distinguish: species sorting resulting from a change in interspecific competitive pressure, and phenotypic plasticity (here explicitly physiological plasticity i.e. species‐specific physiological adjustment). A shift in species composition as well as physiological adjustments in species can lead to changes in fatty acid composition that determine the food quality for zooplankton consumers. We used phytoplankton communities consisting of five species and exposed them to two different light intensities, two light conditions (constant and variable), and two levels of phosphorus supply. Changes in fatty acid and species composition were analyzed. We compared community pairs differing in one factor by calculating the Bray‐Curtis similarity index for the composition of both variables. Comparing the Bray‐Curtis similarity index of the species composition with the index of the fatty acid composition was used to estimate the effects of species sorting and physiological plasticity. Changes in nutrient supply influenced fatty acid responses based on species sorting and physiological plasticity the most. On one hand, the relevance of physiological plasticity was highest at cultivation in different nutrient supplies but the same light environment. Conversely with low nutrients species sorting appeared to dominate the response to changes in light, while at high nutrients physiological plasticity appeared to influence the response. Overall, under low phosphorus supply the communities showed a lower total fatty acid content per carbon and had increased proportions of saturated and monounsaturated fatty acids. Instead, communities in low light produced more of eicosapentaenoic acid. Our results suggest that the relevance of species sorting and physiological plasticity in shaping the community response highly depends on the environmental factors that influence the system. Nutrient supply had the largest effect, while light had more limited conditional effects. However, all of these factors are important in shaping the food quality of the phytoplankton community for higher trophic levels.